Pengaruh Inflasi, Kurs dan BI Rate terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2015-2022 - Fakih Yudhistira; Dorothea Ririn Indriastuti (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research uses qualitative data consisting of inflation, exchange rate, BI rate and Composite Stock Price Index sourced from www.idx.com, www.ojk.go.id, and www.bps.go.id. The data collection technique in this research uses secondary data. The sample in this research was 32. The data analysis technique used descriptive analysis, namely in the form of multiple linear regression analysis, t test, F test, and coefficient of determination test. The results of the t test show that inflation has a significant effect on the stock price index because it has a significance value of 0.027 < 0.05, the BI rate has a significant effect on the stock price index because it has a significance value of 0.027 < 0.05, and the exchange rate has a significant effect on the stock price index because it has a value significance 0.001 <0.05. The results of the F test show a significance value of 0.000 < 0.05, meaning that the model remains in predicting the influence of the independent variables, namely inflation, BI rate and exchange rate on the dependent variable, namely the stock price index. The result of the coefficient of determination is 46.3%, meaning that the influence given by the independent variables, namely inflation, BI rate and exchange rate, has on the dependent variable, namely the stock price index. The remaining 53.7% is influenced by other factors outside the variables studied.